Intramuscular autologous blood therapy - a systematic review of controlled trials - Katja Oomen-Welke; Roman Huber (BMC, 2019)
Abstract Background Autologous whole blood (AWB) is used in complementary medicine for the treatment of infections and skin disorders. So far, the efficacy of AWB is discussed controversially. Methods To estimate the efficacy of AWB therapy and to gather evidence in regard to effector mechanisms, we effected a systematic review of articles accessible through Pubmed and Cambase. Further trials were identified through references and by contacting study authors. Prospective controlled trials concerning intramuscular AWB therapy were included with the exception of trials using oxygenated, UV radiated or heated blood. Information was extracted on the indication, design, additions to AWB and outcome. Full texts were screened for information about the effector mechanisms. Results Eight trials suited our criteria. In three controlled trials about atopic dermatitis and urticaria, AWB therapy showed beneficial effects. In five randomized controlled trials (RCTs), two of which concerned respiratory tract infections, two urticaria and one ankylosing spondylitis, no efficacy could be found. A quantitative assessment was not possible due to the heterogeneity of the included studies. We only found four controlled trials with sample sizes bigger than 37 individuals per group. Only one study investigated the effector mechanisms of AWB. Conclusions There is some evidence for efficacy of AWB therapy in urticaria patients and patients with atopic eczema. Firm conclusions can, however, not be drawn. We see a great need for further RCTs with adequate sample sizes and for investigation of the effector mechanisms of AWB therapy.